EMERGÊNCIA E CRESCIMENTO INICIAL DE GERGELIM COINOCULADO COM AZOSPIRILLUM BRASILENSE E TRICHODERMA HARZIANUM - Alves Gottardi, Gabriel; Alves Gottardi, Guilherme; Eduardo Skittberg Pestana , Carlos; Ito Marcanzoni , Bruno; Abel dos Santos , Benjamin; Zoz, Tiago (ANAIS DO ENIC, 2026)
-